Wanita Karir dan Kepemimpinan Perempuan dalam Perspektif Hukum Islam Kontemporer - Sholihah Nurul Afifah; Naira Nuryaduljannah; Anis Salsabila (Kampus Akademik Publiser, 2026)
This study examines career women and women's leadership from a contemporary Islamic legal perspective. The increasing involvement of women in the workplace and leadership positions has given rise to diverse views in society, particularly within Islamic legal studies. This study aims to analyze Islamic legal perspectives on career women and their role as leaders in the modern era. The method used in this study is a literature review with a qualitative descriptive approach through a review of various literature, scientific journals, and the opinions of Islamic scholars. The results show that Islam provides opportunities for women to work and hold leadership positions, provided they adhere to sharia values ​​and carry out their responsibilities properly. Therefore, women's leadership in the contemporary context is acceptable in accordance with the needs and interests of society.